Mathematical modeling and simulation of a rectangular pulse transceiver operating in the discrete-time domain - Berber, Stevan M. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The paper presents the theory and design issues of a discrete-time communication system used for discrete-time pulse transmission with and without filtering. Signals are analyzed in both the time domain and the frequency domain.Methods: The system is theoretically analyzed using block schematics expressed in terms of mathematic operators and the system simulation is performed to confirm the theoretical findings.Results: Discrete-time signals are presented in the time domain and the frequency domain as well as confirmed by a simulation designed in Matlab.Conclusion: The results of the paper contribute to the theoretical modeling and design of modern discrete communication systems.
Keywords: discrete communication system; system design; discrete pulse transceiver; filtering; correlation receiver